Wahbah al-Zuhailī’s Epistemology of the Religious Freedom Concept: Between Maqāṣid Ḥifẓ al-Dīn and Human Rights - Lathifah, Anthin; Munawwarah, Lathifah; Achmad Gunaryo; Masduki, Anwar; Hidayatulloh, M. Arief (Universitas Islam Negeri Raden Intan Lampung, 2025)
According to the classical ulama, maqāṣid ḥifẓ al-dīn includes faith and worship in the Islamic religion, but it is different from Wahbah al-Zuhailī, who developed the concept of ḥifẓ al-dīn as the epistemological basis of the law of religious freedom as a universal human right. The purpose of this article is to describe Wahbah al-Zuhailī's concept of religious freedom which is based on maqāṣid ḥifẓ al-dīn and the theology of freedom as a universal human right. This article is the result of literature research, where data on the concept of religious freedom according to Wahbah al-Zuhailī were analyzed using a content analysis approach and a thematic analysis related to the law on religious freedom. The results of the research conclude that the epistemology of religious freedom (al-hurriyah al-i'tiqādiyyah) according to Wahbah al-Zuhailī integrates the philosophical foundations of maqāṣid ḥifẓ al-dīn and the theology of religious freedom as an absolute human right from God. Based on the epistemological basis of this law, it produces two concept of freedom of religion: first, there should be no coercion to follow a particular religion as in the verse